Keselarasan Antara Tasawuf dan Kehidupan Nabi Muhammad - Reza Pahlevi Dalimunthe; Muhammad Valiyyul Haqq (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The practice of Sufism in today's society and what the prophet Muhammad did is often conceptual and practical differences. Sufism, which is the sum-sum of Islam, is often the target of attacks on the wrong practices of Sufism that occur today or for ignorance of good and true Sufism. This article tries to describe the life of Sufism, practice, and the spiritual condition of the Prophet Muhammad. In the scientific field and religious side, this will be traced in terms of Sufism practices carried out by the prophet Muhammad found in the hadiths and books. This journal was analyzed using qualitative methods of literature study. Related primary and secondary sources will be categorized which will be presented in the form of research results. Various sources that the author can reveal that the life of the prophet Muhammad was filled with Sufistic instruments, and a lifestyle like this is an ideal lifestyle. It can be concluded that this pattern of life is at the same time a treasure and 'ibrah for the Sufi life, so it can be said that the Messenger of Allah has laid the spiritual foundations for his followers throughout the ages.